Spontaneous heterotopic pregnancy. Report of two cases - Monzón Castillo, Eli Pedro (2019)
Heterotopic pregnancy is the simultaneous development of an intrauterine and an ectopic pregnancy. This complication is increasing due to infertility treatment, especially assisted reproduction techniques. There are two types: induced (associated with in vitro fertilization techniques, rate 1:1 000 to 1: 1 500 pregnancies) or spontaneous (1:20 000 to 1:80 000 pregnancies). Causal factors for spontaneous heterotopic pregnancies include pelvic inflammatory disease, use of intrauterine device or hormonal devices, previous pelvic surgery, and history of ectopic pregnancy. We present two cases of spontaneous heterotopic pregnancies.